Burden of malignant melanoma in Ukraine in 2002–2013: incidence, mortality and survival - Korovin, S.; Fedorenko, Z.; Michailovich, Yu.; Kukushkina, M.; Sekerija, M.; Ryzhov, A. (PH Akademperiodyka, 2023)
Summary. Background: The malignant melanoma (MM) incidence rates were increasing and later stabilizing in many regions of the world, while in South-Eastern Europe incidence rates are uniformly increasing and mortality rates are higher. Aim: To describe burden of MM in Ukraine in terms of incidence, mortality and survival by sex, age and stage for the period 2002–2013 and compare with European countries. Materials and Methods: Database of the National Cancer Registry of Ukraine was used to extract MM incidence cases; number of MM deaths was obtained from the official mortality statistics. Age-standardised and age-specific incidence and mortality rates were calculated by sex, age groups (15–39, 40–59 and 60+); estimated annual percent of change was used to describe trends. Proportions of new cases by stage of disease and calendar period (2002–2007 vs 2008–2013) were compared as well as net survival estimates. Results: In Ukraine, MM was more common in females (age-standardised 5.3 per 100,000 in 2013; annual percent of change 3.5%) than in males (5.1 per 100,000; 4.1%); around 50% of them diagnosed in the age group 60+. The observed increase in proportion of new cases with early stage (I–II) was due to stage II cases. The slight increase in mortality rates in males or stability in females were not accompanied with increase of survival. Net MM survival was consistently lower comparing to European countries. Conclusion: More resources should be targeted to increase the capacity of healthcare in diagnostics and treatment of malignant melanoma, but also in promoting healthcare and education in Ukraine.